Successful Treatment of Uterine Arteriovenous Malformation due to Uterine Trauma - Burak Karadag; Onur Erol; Ozgur Ozdemir; Aysel Uysal; Ahmet Sukru Alparslan; Cemil Gurses; Mert Koroglu (Hindawi Limited, 2016)
Uterine arteriovenous malformation (AVM) is defined as abnormal and nonfunctional connections between the uterine arteries and veins. Although the patients typically present with vaginal bleeding, some patients may experience life-threatening massive bleeding in some circumstances. The treatment of choice depends on the symptoms, age, desire for future fertility, and localization and size of the lesion; however, embolization of the uterine artery is the first choice in symptomatic AVM in patients at reproductive age with expectations of future fertility. We report a case of acquired AVM (after D/C) with an extensive lesion, which was successfully treated with bilateral uterine artery embolization (UAE).